Effects of D-Mannose, ElliroseTM and Lactobacillus Plantarum in treatment of urinary tract recurrent infections (rUTIs): A survey of urologists knowledge about its clinical application. - Milandri, Riccardo; Bocchialini, Tommaso; Maltagliati, Matteo; Michele, Cotugno; Simonetti, Elisa; Stefania, Ferretti; Maestroni, Umberto Vittorio; Rocco, Bernardo Maria Cesare; Micali, Salvatore (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Urinary tract infections (UTIs) and recurrent urinary tract infections (rUTIs) are widespread disease and almost half of all women will experience at least one episode of cystitis during their life. Aim of this study was to review the evidence of literature about the therapeutic and preventive effects of a product containing D-Mannose, ElliroseTM and Lactobacollus Plantarum on patients’ symptoms, quality of life and recurrence of UTIs and to investigate the practicing urologists’ knowledge about the clinical application of this product. Materials: We administrated an investigational survey about clinical use of a phytotherapeutic product made of D-Mannose, ElliroseTM and Lactobacollus Plantarum to 12 residents in Urology at the University of Modena and Reggio Emilia and to 32 urologists working in the provinces of Modena, Reggio Emilia and Parma. Results: 61% of physicians have diagnosed rUTIs in 3-6 patients during a month, and 7% of them in more than 6 patients during the same period of time. By these results rUTIs appear as common pathological conditions. 59% prescribed the product at least 1 time a month and 14% prescribed it more than 5 times. 43% administrated the product after out-patient invasive examinations as cistoscopy and urodynamic exam for UTIs prevention. 55% noticed a significant improvement in patient’s QoL (Quality of Life) suffering from rUTIs. Furthermore 48% also reported a significant effect for the improvement of urinary symptoms of patients. No gastric or general side effects have been noticed during the administration period. Finally the cost of integrator has been reported affordable for the great majority of patients. Conclusions: Many studies in Literature have shown that D-Mannose and H. sabdariffa (ElliroseTM) reduce the risk of development of rUTIs opposing colonization and proliferation of uropathogenic bacteria in urinary tract. Our investigational survey about the administration of a phytotherapeutic product showed that this product is well-known and has a proved positive impact.